Pre-Abortion Decision-Making Conflict in Pregnant Women Seeking Legal Abortion - Khodabandeh, Farideh; Kahani, Vida (Novelty in Biomedicine, 2020)
Background: Woman’s decision-making for abortion entails understanding and assessing those options in the context of her unique situation, feelings, aspirations and beliefs. The objective of this study was to examine decision–making conflict and all relevant factors, among women seeking legal abortion authorization letter, referred to Legal Medical Centre in Tehran. Materials and Methods: In this cross-sectional study, decision-making conflict assessed using the decisional conflict scale (DCS) among 282 pregnant women in their first trimester. Descriptive and logistic regression analyses were undertaken to describe and explore collected data. Results: Eligible women requesting legal abortion were mostly in age group 25-34 years old (50.4% .142, M=31.55, SD=6.1, ranging from 17 - 46 years). They were mostly in gestational age<16 weeks, (212, 75.2%), with average 14.67 (SD=3.51), range 15.0 weeks (4-19 weeks). Some decision conflict (DCS score 25 or greater) was experienced by 182 (64.5%) participants. Conclusion: Women seeking legal abortion may go against their own sense of right and wrong. They deserve pre-abortion consulting to deal with conflict and negative effects in decision-making.